Global change biology the study of life on a rapidly changing planet - Rosenblum, Erica Bree (New York Oxford University Press, 2021)
Bree Rosenblum's Global Change Biology provides a comprehensive introduction to the field of Global Change Biology and a roadmap for structuring Global Change Biology courses, a burgeoning field of biological study. The first of its kind, Rosenblum goes beyond the narrow focus of existing texts, which tend to focus on climate only, by offering a conceptionally integrated approach to understanding how humans have impacted life on Earth. The textbook guides students to think about change across spatial and temporal scales and fills a unique niche of integrating ecological and evolutionary perspectives throughout.
Recommend by Prof. Brisneve Edullantes
Includes bibliographical references and index.
Keywords: Climatic changes; Ecology; Global environmental change